Peningkatan Kemandirian Anak Melalui Strategi My Morning Mission Berbasis Life Skill Islami di RA Nurul Huda Semarang - Ulya Ainur Rofi'ah; Widya Fajar Oktaviana; Ainur Rosyidah Kusuma; Rifatul Khotimah (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to enhance the independence of children aged 4–5 years through the “My Morning Mission” strategy based on Islamic life skills at RA Nurul Huda Semarang. The method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. Children’s independence was measured through four indicators: (1) the ability to wear shoes and organize prayer equipment, (2) the ability to complete tasks without assistance, (3) the courage to make simple decisions independently, and (4) responsibility for personal belongings and the surrounding environment. The research findings show a significant improvement in all indicators of independence from Cycle I to Cycle II. Most children reached the Very Well Developed (BSB) category, indicating that this strategy effectively fosters independence while also instilling Islamic values through consistent, enjoyable, and meaningful daily activities. This study recommends the implementation of the “My Morning Mission” strategy as a character-based learning approach that can be sustainably integrated into early childhood education programs.